Examining the Effectiveness of the Imago Therapy Approach on Marital Adjustment and Love Styles in Married Students with Early Marriages - Khatibi, Jamileh; Haji Arbabi, Fatemeh; Fariborzi, Elham (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This study aimed to investigate the effectiveness of the Imago therapy approach on marital adjustment and love styles in married students with early marriages. Methods and Materials: The research employed a semi-experimental method with a pre-test and post-test design with a control group. The statistical population studied included second-year high school students from vocational and technical schools in Mashhad during the 2021-2022 academic year. A purposive sampling method was used, and the participants were randomly assigned to a 15-member experimental group and a 15-member control group. The experimental group underwent 10 sessions of Imago therapy intervention and training. Subsequently, post-tests were conducted using questionnaires on both groups, and follow-up tests were administered at the end. To measure the level of marital adjustment, the Spanier Marital Adjustment Questionnaire (1976) was used, and to assess attitudes toward love, the Hendrick Love Attitudes Scale (1986) was utilized. The data were analyzed using inferential statistics through the SPSS statistical software. Findings: The results of the covariance analysis indicated that the Imago therapy model was effective in increasing marital adjustment and love styles, suggesting that this approach can be used in therapeutic and counseling sessions. Conclusion: The findings of this study indicate that Imago therapy significantly improves marital adjustment and love styles in married students with early marriages. Post-intervention scores in the experimental group showed a meaningful increase in marital adjustment and strong attitudes toward love compared to the control group. Thus, Imago therapy is an effective intervention for enhancing marital satisfaction and relationship quality in this population.